An Integrative Clustering Approach to tDCS Individual Response Variability in Cognitive Performance: Beyond a Null Effect on Working Memory. (1st September 2020) - Luque-Casado, Antonio; Rodríguez-Freiría, Rocío; Fogelson, Noa; Iglesias-Soler, Eliseo; Fernández-del-Olmo, Miguel
Highlights: Anodal tDCS did not improve working memory performance. A subgroup of 'responders' was identified among the total sample. There was a high variability in the individual response pattern. Inter-individual variability may affect the reliability of tDCS research. Abstract: Despite the growing interest in the use of transcranial direct current stimulation (tDCS) for the modulation of human cognitive function, there are contradictory findings regarding the cognitive benefits of this technique. Inter-individual response variability to tDCS may play a significant role. We explored the effects of anodal versus sham tDCS over the left prefrontal cortex (LPFC) on working memory performance, taking into account the inter-individual variability. Twenty-nine healthy volunteers received an 'offline' anodal tDCS (1.5 mA, 15 min) to the left prefrontal cortex (F3 electrode site) in an intra-individual, cross-over, sham-controlled experimental design. n-back and Sternberg task performance was assessed before (baseline), immediately after tDCS administration (T1) and 5 min post-T1 (T2). We applied an integrative clustering approach to characterize both the group and individual responses to tDCS, as well as identifying naturally occurring subgroups that may be present within the total sample. Anodal tDCS failed to improve working memory performance in the total sample. Cluster analysis identified a subgroup of 'responders' who significantly improved their performance after anodal (vs. sham) stimulation, although not to a greater extent than the best baseline or sham condition. The proportion of 'responders' ranged from 15% to 59% across task conditions and behavioral outputs. Our findings show a high inter-individual variability of the tDCS response, suggesting that the use of tCDS may not be an effective tool to improve working memory performance in healthy subjects. We propose that the use of clustering methods is more suitable in identifying 'responders' and for evaluating the efficacy of this technique.